The Character and Work Ethos of Muslim Marketers in Modern Business Competition - Novita Safitri (Journal of Islamic Economics Management and Business (JIEMB), 2026)
The increasingly fierce competition in modern business, influenced by the development of digital technology and changing consumer behavior, demands marketing practices that are not only profit-oriented but also uphold ethical values and moral responsibility. In this context, Islamic marketing emerges as an approach that places Islamic values as the primary foundation for every marketing activity. This research aims to examine the character and work ethic of Muslim marketers in the face of modern business competition and to explain their role as a source of sustainable competitive advantage. The research method used is descriptive qualitative with a literature study approach. Data was obtained from various relevant library sources, such as scientific journals, books, and academic publications related to Sharia marketing and Islamic work ethic. The study results show that the characteristics of Muslim marketers that reflect honesty, trustworthiness, professionalism, and moral responsibility, as well as the Islamic work ethic that views work as worship, play an important role in building consumer trust, business reputation, and business sustainability amidst the dynamics of modern business competition